Ethics Dumping Case Studies from North-South Research Collaborations (SpringerBriefs in Research and Innovation Governance,, 2018)
This book is published under a CC BY 4.0 license. This book provides original, up-to-date case studies of "ethics dumping" that were largely facilitated by loopholes in the ethics governance of low and middle-income countries. It is instructive even to experienced researchers since it provides a voice to vulnerable populations from the forementioned countries. Ensuring the ethical conduct of North-South collaborations in research is a process fraught with difficulties. The background conditions under which such collaborations take place include extreme differentials in available income and power, as well as a past history of colonialism, while differences in culture can add a new layer of complications. In this context, up-to-date case studies of unethical conduct are essential for research ethics training.